TOR 2020
DOI: 10.47967/qkty9216
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration: Exploring the PGR Superpower for Addressing Inequalities within Academia

Abstract: Inequalities within academia are rampant. Sexism, racism, classism and discrimination impose huge barriers to those entering academic work or study. These issues are amplified in times of crisis, such as COVID-19. As postgraduate researchers, we can often feel powerless to address these inequalities. We possess little status in academic power structures, and as such it can be difficult to ‘rock the boat’ or diverge from normalised patterns of discrimination within our fields. In this essay, I argue that while … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…For example, a recent study showed how academic papers that are tweeted receive more coverage and citations than papers that have no Twitter presence (Luc et al, 2021). Similarly, Twitter can be a useful place to forge academic collaborations (e.g., Prosser, 2020), engage in science communication and outreach, and "keep up" with academic conferences (Letierce et al, 2010). This demonstrates the advantage that scholars with an active Twitter presence have, allowing them to more readily "compete" in the neoliberal academic environment, while also gaining all-important access to the "hidden curriculum", or "insider knowledge", of mainstream academia.…”
mentioning
confidence: 99%
“…For example, a recent study showed how academic papers that are tweeted receive more coverage and citations than papers that have no Twitter presence (Luc et al, 2021). Similarly, Twitter can be a useful place to forge academic collaborations (e.g., Prosser, 2020), engage in science communication and outreach, and "keep up" with academic conferences (Letierce et al, 2010). This demonstrates the advantage that scholars with an active Twitter presence have, allowing them to more readily "compete" in the neoliberal academic environment, while also gaining all-important access to the "hidden curriculum", or "insider knowledge", of mainstream academia.…”
mentioning
confidence: 99%